The Anticancer Mechanism Of Ibuprofen Or Indomethacin In Colorectal Cancer Cells [RS431.A64 K45 2007 f rb]. - Khoo, Boon Yin (2007)

(untitled)
non-steroidal anti-inflammatory drugs (NSAIDs) for their anticancer activities. Besides being non-selective cyclooxygenase-2 (COX-2) inhibitors, both NSAIDs are also direct ligands for peroxisome proliferators-activated receptor-gamma (PPAR).